'Conscientious objection' and canon law. Issue 1 (2nd January 2021) - Costigane, Helen
Abstract : The recent case of the Glasgow midwives, Mary Doogan and Concepta Wood, highlighted again the scope of the 'conscience clause' relating to the Abortion Act 1967, and to which tasks it could be applied in relation specifically to their role as Labour Ward Co-ordinators. However, as members of the Catholic Church, this case had specific resonances for them in relation to their beliefs, both from a moral-theological and canonical perspective, the latter of which carries potential ecclesiastical penalties. This article looks at the decisions handed down by the courts, and analyses the issues arising in relation to principles of Catholic morality and the relevant canons in the 1983 Code of Canon Law.